2019
DOI: 10.3390/en12244613
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of a Distributed Energy System under Different Control Strategies with a Conventional Energy System

Abstract: The distributed energy system (DES) has increasingly attracted considerable attention from researchers due to its environmental friendliness and high efficiency. In the hot summer and cold winter areas, DES is an efficient alternative for district cooling and heating. A case study located in Changsha, China, which is a typical hot summer and cold winter area, is analyzed. Four control strategies are proposed in this study. The four cases under different control strategies are compared in terms of energy, econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Signs of the performance gap as discussed in this research started appearing from the mid-1990s [48] and are still discussed as a core issue [20,40,49]. This gap is addressed in a diverse context in different studies, such as the difference between predicted and actual energy performance of a building, including all the complications of sub-systems, occupant behavior, atmospheric conditions, control settings, and others [5,27,28]. Tang et al [5] found that a primary energy saving between 36.7% to 48% is attainable by introducing a distributed energy system in buildings.…”
Section: Energy Performance Gapmentioning
confidence: 94%
See 3 more Smart Citations
“…Signs of the performance gap as discussed in this research started appearing from the mid-1990s [48] and are still discussed as a core issue [20,40,49]. This gap is addressed in a diverse context in different studies, such as the difference between predicted and actual energy performance of a building, including all the complications of sub-systems, occupant behavior, atmospheric conditions, control settings, and others [5,27,28]. Tang et al [5] found that a primary energy saving between 36.7% to 48% is attainable by introducing a distributed energy system in buildings.…”
Section: Energy Performance Gapmentioning
confidence: 94%
“…This gap is addressed in a diverse context in different studies, such as the difference between predicted and actual energy performance of a building, including all the complications of sub-systems, occupant behavior, atmospheric conditions, control settings, and others [5,27,28]. Tang et al [5] found that a primary energy saving between 36.7% to 48% is attainable by introducing a distributed energy system in buildings. Further, a control strategy combining geothermal and solar energies is recommended due to its good performance and high flexibility.…”
Section: Energy Performance Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…The main goal of the electric utility is concise for providing electrical as may be demanded by the customers at the lowest possible operating cost, in tandem with maintaining the system security, reliability, and economics of the system. Furthermore, reducing the environmental damage caused by the conventional thermal units, guaranteed consistent supply of energy on the secure condition and reducing the electricity bills of customers are parts of the goal [1][2][3]. However, load demand variation is largely uncontrollable, with any interruptions very costly.…”
Section: Introductionmentioning
confidence: 99%